Pengaruh Insentif Dan Kecerdasan Intelektual Terhadap Efisiensi Kerja Karyawan Pada Perusahaan X Tahun 2023 - Edy Edy; Free Antonius Simanjuntak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study was conducted at Company X in 2023. The purpose of this study was to determine and analyze the effect of incentives and intellectual intelligence on the work efficiency of Company X employees in 2023. The population amounted to 35 employees while the sample in this study is: 35 employees. The sampling technique used is saturated sampling. The technique of data collection is the distribution of questionnaires, interviews and documentation studies and literature studies. Data analysis using multiple linear regression análisis. The conclusion in the study that simultaneously incentives and intellectual intelligence have a positive and significant effect on the work efficiency of Company X employees in 2023. Partially, incentives have a positive and significant effect on the work efficiency of Company X employees in 2023. Partially N intellectual intelligence has a positive and significant effect on the work efficiency of Company X employees in 2023. Adjusted R Square is: equal to 0.473 means that incentives and intellectual intelligence can explain the work efficiency of Company X employees in 2023 by 47.3% and the remaining 52.7% (100-47. 3) are influenced by other variables outside of this study such as: salary, promotion and so on